The polypill: the solution for prevention of coronary heart disease? - Natadidjaja, Hendarto (Universa Medicina, 2009)
In Western countries, cardiovascular disease is the most common cause of death and it is expected that it will continue to be so in the near future.(1) If the resulting physical impairment and psychosocial disturbances are also taken into account, clearly this is a serious problem from the viewpoint of productivity, quality of life, as well as community health level. Therefore the institution of preventive measures is an important issue. Unfortunately, however, currently preventive measures that are effective, safe, and at the same time practical and economical, are almost nonexistent.